2012
DOI: 10.1145/2231816.2231817
|View full text |Cite
|
Sign up to set email alerts
|

Micro perceptual human computation for visual tasks

Abstract: Human computation (HC) utilizes humans to solve problems or carry out tasks that are hard for pure computational algorithms. Many graphics and vision problems have such tasks. Previous HC approaches mainly focus on generating data in batch, to gather benchmarks or perform surveys demanding non-trivial interactions. We advocate a tighter integration of human computation into online, interactive algorithms. We aim to distill the differences between humans and computers and maximize the advantages of both in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Amazons Mechanical Turk is pioneering on-demand crowdsourcing that can draw on human computation or social computing systems. Research projects are exploring how this can be used for path planning [31], to determine depth layers, image normals, and symmetry from images [32], and to refine image segmentation [33]. Researchers 4 are working to understand pricing models [34] and apply crowdsourcing to grasping [35].…”
Section: E Crowdsourcing and Call Centersmentioning
confidence: 99%
“…Amazons Mechanical Turk is pioneering on-demand crowdsourcing that can draw on human computation or social computing systems. Research projects are exploring how this can be used for path planning [31], to determine depth layers, image normals, and symmetry from images [32], and to refine image segmentation [33]. Researchers 4 are working to understand pricing models [34] and apply crowdsourcing to grasping [35].…”
Section: E Crowdsourcing and Call Centersmentioning
confidence: 99%
“…Gingold et al [6] introduced a technique for applying the perception of a crowd to the analysis of 2D images. Chaudhuri et al [5] proposed AttribIt, an interface using semantic attributes for designing visual content, where they utilized crowds to learn the semantic attributes of design components.…”
Section: Crowd-powered Analysismentioning
confidence: 99%
“…Thus, we take a pairwise comparison approach [19,6,5] in which crowd workers are shown a pair of designs and asked to choose the best one. As a result, relative scores instead of absolute ones are obtained.…”
Section: Gathering Pairwise Comparisons By Crowdsourcingmentioning
confidence: 99%
“…The use of crowdsourcing to collect data is gaining adoption, and has been used in recent approaches to a range of problems, including understanding shape through gauge figures [Cole et al 2009], creating a mesh segmentation database [Chen et al 2009], devising a retargeting evaluation framework [Rubinstein et al 2010], and for integrating humans into the loop for microtasks [Gingold et al 2012]. The experiences from this body of prior work has informed our design process.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to providing positive feedback, we found it was necessary to prevent 159 users from doing our tasks because they were either malicious or had an accuracy below 50%. The use of sentinels is recommended by [Gingold et al 2012] to check labeler quality. However, we found that our tasks are not amenable to this approach since our surfaces occur in distinctive photographs, and repetition tips off the labeler.…”
Section: Task Analyticsmentioning
confidence: 99%